Caminos que la filantropía puede abrir - Gutiérrez, Roberto; Lobo, Iván Darío (Sociedad y Economía, 2006)
The debate on the real impact of philanthropic initiatives is frequent. There are two key issues underlying that debate. On the one hand, how sustainable those initiatives are; on the other, how relevant are they to effectively address social needs. This article contributes to the debate by stating that philanthropy is relevant insofar as it generates social value in one of four possible ways: by opening new markets, participating in value chains, strengthening institutions, and influencing public policy. In the first part we examine some of the basic features of philanthropic initiatives of organizations, emphasizing the way in which they can increase their sustainability. Then we describe the way those initiatives create social value and how they relate to economic value. Finally, we focus on the analysis of some for-profit and non-profit Colombian organizations that expose the promises and shortcomings of philanthropy.